Income from Bonds : Treatment in the System of National Accounts 1993 - Laliberte, Lucie (IMF Working Papers; Working Paper ;, 2002)
How to account for interest on bonds in a system as integrated as the System of National Accounts 1993 (1993 SNA) has been a source of much controversy. Two main positions emerge: the debtor treatment based on the contractual arrangements of the bonds; and the creditor treatment based on current interest rates and prices of assets/liabilities. Using the discounted cash flow model, this paper explores the treatment of income and other benefits from assets in the 1993 SNA. It finds that the debtor approach to bond interest conforms with the 1993 SNA recording income and other benefits from assets, as that approach captures the results of effective decision making between institutional units.